Survei Awareness Mahasiswa PGSD UNM Bone Terhadap Teknologi Virtual Reality - Achmad Shabir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
Virtual reality technology is experiencing rapid development in the global market, but not in the Indonesian market. When other parts of the world took advantage of this technology for online learning during the Covid-19 pandemic, something similar was almost never happened in Indonesia. This research seeks to research the awareness level of students of PGSD UNM Kampus VI Bone towards virtual reality. The survey method was carried out on 160 samples who were randomly selected from a population of 571 students, whose characteristics tended to be homogeneous. The results showed that the level of awareness of VR technology was still low (index 0.36). The run test also shows that the selected sample is indeed random, so the study assumed to be well-represent the population. It is recommended to the stakeholders, for increasing promotion and ease the access to virtual reality technology so level of awareness can be increased.